Penerapan Algoritma First Come First Served dalam Menentukan Penyewaan Lapangan Futsal Berbasis Web - Rizky Ramadhan; Fauziah Fauziah; Endah Tri Esti Handayani (KITA Institute, 2022)
Until now, the Go Futsal field rental system located in Lebak Bulus still uses a manual nature and in processing futsal field transactions there is no desktop-based information system. In addition, the customer must also come to the location and make payments that still use paper as evidence, making it difficult for officers to process data. To overcome this problem, a futsal field rental application using a computer is needed. With this application, it is easier for officers to work using a computer. This futsal field rental information system can also minimize unwanted events such as lost or damaged data. First Come First Served which is applied to this application where the customer who first ordered will be served first. PHP coding and MySQL database are used in this application system. Testing this application using the Black box testing method. From the above writing that has been made and the previous stages that have been carried out starting from design to implementation, it can be concluded that the futsal field rental website application system using the First Come First Served algorithm can help solve problems that exist on the Go Futsal field in terms of the interface. as well as systems and make it easier for users who want to rent a futsal field online who don't have to come to the location and also make it easier to view field schedule information.